1997
DOI: 10.1177/154079699702200206
|View full text |Cite
|
Sign up to set email alerts
|

Accountability for All Students: Kentucky's Alternate Portfolio Assessment for Students with Moderate and Severe Cognitive Disabilities

Abstract: One of the keys to ensuring high expectations for all students is the requirement for inclusive measures of educational accountability. Recognizing this need, Congress enacted Title II, National Education Reform Leadership, Standards, and Assessments, calling for the development of state assessment systems that fully include all students, as a major component of the 1994 Goals 2000: Educate America Act. At present, Kentucky is the only state in the nation that fully includes all students within a statewide edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 8 publications
(9 reference statements)
2
58
1
Order By: Relevance
“…While these changes in instructional practices and communication outcomes for students with significant disabilities were not necessarily the result of the alternate assessment, they were supported by that assessment. Turner, Baldwin, Kleinert, and Kearns (2000) and Kleinert et al (1997) found a moderately strong correlation between alternate assessments scores and the implementation of best practices for students with significant disabilities at the school or classroom level. Thus, high student scores tended to be a reflection of effective instructional programming.…”
Section: University Of Kentuckymentioning
confidence: 95%
See 1 more Smart Citation
“…While these changes in instructional practices and communication outcomes for students with significant disabilities were not necessarily the result of the alternate assessment, they were supported by that assessment. Turner, Baldwin, Kleinert, and Kearns (2000) and Kleinert et al (1997) found a moderately strong correlation between alternate assessments scores and the implementation of best practices for students with significant disabilities at the school or classroom level. Thus, high student scores tended to be a reflection of effective instructional programming.…”
Section: University Of Kentuckymentioning
confidence: 95%
“…At least one state, Indiana, has designed a statewide electronic portfolio for alternate assessments (Bennett & Davis, in press). Essential to any of these methods of assessment is a reliable method for scoring, which may prove especially difficult for portfolio assessments (see Kleinert, Kearns, & Kennedy, 1997).…”
Section: University Of Kentuckymentioning
confidence: 99%
“…However, a goal of several states' alternate assessment systems, par, ticularly those using portfolios (Kleinert, et al, 1997;Kleinert & Thurlow, 2001), is to capture the educational opportunities provided to students with significant disabilities. Homogenizing these opportunities is not likely to provide students with highly diverse needs access to richer educational experiences.…”
Section: Specific Criteria Evidenced By a Scoringmentioning
confidence: 99%
“…Kleinert et al (1997) proposed that "one of the keys to ensuring high expectations for every child is requiring that all students be included in measures of educational accountability" (p. 88). Kentucky was the first state to realize that "all means all" and to identify a way to include students with the most significant disabilities in its accountabil- Kleinert, Garrett, et al (2002) Relationship between AA scores and postschool outcomes…”
Section: P R O M I S E S O F a L T E R N A T E A S S E S S M E N Tmentioning
confidence: 99%